Magnetic Resonance Imaging Assisted by Wireless Passive Implantable Fiducial e-Markers - Gokyar, Sayim (2018)
This paper reports a wireless passive resonator architecture that is used as a fiducial electronic marker (e-marker) intended for internal marking purposes in magnetic resonance imaging (MRI). As a proof-of-concept demonstration, a class of double-layer, sub-cm helical resonators were microfabricated and tuned to the operating frequency of 123 MHz for a three T MRI system. Effects of various geometrical parameters on the resonance frequency of the e-marker were studied, and the resulting specific absorption rate (SAR) increase was analyzed using a full-wave microwave solver. The B1+ field distribution was calculated, and experimental results were compared. As an exemplary application to locate subdural electrodes, these markers were paired with subdural electrodes. It was shown that such sub-cm self-resonant e-markers with biocompatible constituents can be designed and used for implant marking, with sub-mm positioning accuracy, in MRI. In this application, a free-space quality factor (Q-factor) of approximately 50 was achieved for the proposed resonator architecture. However, this structure caused an SAR increase in certain cases, which limits its usage for in vivo imaging practices. The findings indicate that these implantable resonators hold great promise for wireless fiducial e-marking in MRI as an alternative to multimodal imaging.